2009
DOI: 10.3945/jn.108.101022
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional Iron and Folate Status Is Inadequate among Married, Nulliparous Women in Rural Bangladesh

Abstract: Recent evidence suggests that poor fetal growth is associated with preconception anemia and first trimester iron deficiency. Periconceptional iron and folate supplementation may improve the effectiveness of iron supplementation programs during pregnancy by treating preexisting anemia, building iron stores, and reducing risk of neural tube defects. Our objective in this study was to describe the iron and folate status of married, nulliparous women in rural Bangladesh from March to May 2007. Of 272 women, 37% we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
18
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
6
18
1
1
Order By: Relevance
“…Data from this study suggested that preconception health promotion messages should combine advice on preconception folic acid supplementation, correction of anaemia and correction of body weight prior to conception. These messages would also be applicable to women in other LMIC settings as similar high prevalence of undernutrition and anaemia have been reported in Vietnam and Bangladesh [9,10]. That obesity is also an emerging risk in other low income settings has been reported for women in Nepal and Bangladesh [22].…”
Section: Environmental Exposuresmentioning
confidence: 87%
See 1 more Smart Citation
“…Data from this study suggested that preconception health promotion messages should combine advice on preconception folic acid supplementation, correction of anaemia and correction of body weight prior to conception. These messages would also be applicable to women in other LMIC settings as similar high prevalence of undernutrition and anaemia have been reported in Vietnam and Bangladesh [9,10]. That obesity is also an emerging risk in other low income settings has been reported for women in Nepal and Bangladesh [22].…”
Section: Environmental Exposuresmentioning
confidence: 87%
“…The prevalence of preconception risk factors has been reported from studies, and ongoing surveillance [5][6][7][8]. Most of these reports are however from women in high income countries (HICs), where the general health status, awareness and education levels are higher than those from low and middle-income countries (LMICs) [9][10][11]. Data on risk exposures of women in low income settings are needed, as these exposures are likely to be dissimilar due to differences in socio-economic, demographic, cultural, dietary, lifestyle, environmental, regulatory and health systems characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This survey also highlights a nationwide high prevalence of zinc deficiency (57.5 %) but low iron deficiency (7.1 %) among rural women. Some other recent studies from Bangladesh have reported iron deficiency among the rural women from 0.0 % [15] to 11.0 % [16].…”
Section: Introductionmentioning
confidence: 88%
“…The study attributed this very low prevalence of Fe deficiency to drinking groundwater from tube wells that were a rich source of naturally occurring Fe. In addition, a few other studies have reported a low prevalence of Fe deficiency of 8 %, 13 % and 17 % among pregnant women, married nulliparous women and schoolchildren, respectively (4)(5)(6) . The present paper aimed to explore the association of groundwater Fe with population-level Fe nutrition and Hb status, at a nationwide scale.…”
mentioning
confidence: 98%